INTEGRATING GENERATIVE AI (GROK.AI) INTO THE DEVELOPMENT OF PERSONALIZED ENGLISH TEACHING MEDIA IN KINDERGARTEN - Guniar Larasati; Mauly Halwat Hikmat (STKIP Persada Khatulistiwa Sintang, 2026)
This study investigates the process of Integrating Generative Artificial Intelligence, specifically Grok.ai, into the development of personalized English teaching media in kindergarten. Adopting a descriptive qualitative approach, this study was conducted at TK Kartika XV-3, Kartasura, Sukoharjo, Central Java, with 41 students participating in an English lesson on the theme of Occupations and Workplaces. Data were collected through direct observation, semi-structured interviews with the classroom teacher, and documentation of the AI-generated media and classroom activities. Data analysis followed Miles, Huberman, and Saldaña’s (2014) interactive model. Findings reveal that Grok.ai was integrated through a deliberate two-stage process: (1) the creation of personalized flashcards in which each student’s photograph was transformed via AI-generated image editing to depict the child wearing a professional costume, and (2) the development of differentiated worksheets tailored to the distinct proficiency levels of two student groups. Both stages required carefully crafted prompts and iterative refinement cycles to produce outputs that were visually appropriate and pedagogically usable. These findings confirm that effective integration of generative AI in early childhood English teaching media demands deliberate prompt literacy and systematic pre-observation of student needs, and that Grok.ai is an effective tool for creating personalized, developmentally appropriate English teaching materials in Indonesian kindergartens.Keywords: English Teaching; Generative AI; Grok.ai; Kindergarten; Personalized Media